COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH IN MODERN LANGUAGE EDUCATION: PRINCIPLES, CHALLENGES AND PRACTICAL APPLICATIONS - Pardayeva Sevinch; Odiljonova Asal (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Communicative Language Teaching (CLT) is an approach to language teaching that emphasizes interaction as both the means and the ultimate goal of learning a language. This article provides an extensive analysis of the CLT methodology, focusing on its implementation in contemporary educational settings. The study explores how CLT shifts the focus from traditional grammatical competence to communicative competence, enabling learners to use the language effectively in real- life interpersonal exchanges. This comprehensive review discusses the core principles of the approach, such as student-centered learning, the use of authentic materials, and the critical balance between fluency and accuracy. Furthermore, the article delves into the specific classroom activities that facilitate active communication, including role- plays, information gaps, and collaborative problem-solving tasks. Despite its widely recognized benefits in improving speaking and listening skills, the implementation of CLT is not without challenges. The paper addresses significant hurdles such as managing large class sizes, the transition for teachers trained in traditional methods, and the complexities of assessing communicative proficiency. Through a detailed examination of current pedagogical theories by scholars like Richards, Rodgers, and Brown, this article argues that CLT remains a vital and dynamic framework for language acquisition in a globalized world. The findings suggest that while a hybrid approach might be necessary for certain contexts, the fundamental communicative goals of CLT are essential for developing true linguistic autonomy. This article aims to provide educators with a clear blueprint for integrating CLT strategies into their daily teaching practice to enhance student engagement and outcomes.